2021
DOI: 10.1111/tbed.14279
|View full text |Cite
|
Sign up to set email alerts
|

Pathological analysis and genetic characterization of the first outbreak H5N8 subtype avian influenza virus isolated from wild swan in Shandong, China

Abstract: In January 2021, an outbreak of H5N8 subtype avian influenza was identified from wild mute swans (Cygnus olor) in an overwintering site located within Yellow River Delta Nature Reserve in Shandong, China, for the first time. We sequenced the hemagglutinin (HA) and neuraminidase (NA) genome segments of the virus, named A/mute swan/Shandong/1/2021 (H5N8), and explored the genetic characterization and comparative phylogenetic analysis to track its origin. The wild swans prior to death showed nervous signs accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The whole-virion inactivated influenza vaccine is the main strategy for an avian influenza vaccine design for human use, while the development of a vaccine candidate virus is essential for pandemic preparedness. It has been found that the HA of various avian influenza viruses contains multi-basic cleavage sites that are lethal to chickens, such as arginine (R) and lysine (K) sites in H5Nx and H7Nx [ 7 ], and REKRRKR/GLF in H5N8 [ 8 ]. After deleting the polybasic amino acids at the HA cleavage site of the HPAI parent virus, the new modified HA, along with the NA of the wild virus and the six internal segments of the backbone (such as A/PR/8/1934 H1N1 virus) is frequently used to generate a new low pathogenic virus as a vaccine candidate virus by reverse genetics (RG) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The whole-virion inactivated influenza vaccine is the main strategy for an avian influenza vaccine design for human use, while the development of a vaccine candidate virus is essential for pandemic preparedness. It has been found that the HA of various avian influenza viruses contains multi-basic cleavage sites that are lethal to chickens, such as arginine (R) and lysine (K) sites in H5Nx and H7Nx [ 7 ], and REKRRKR/GLF in H5N8 [ 8 ]. After deleting the polybasic amino acids at the HA cleavage site of the HPAI parent virus, the new modified HA, along with the NA of the wild virus and the six internal segments of the backbone (such as A/PR/8/1934 H1N1 virus) is frequently used to generate a new low pathogenic virus as a vaccine candidate virus by reverse genetics (RG) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%